Molecular and Phenotypic Detection of Some of the Coded Genes for Virulence Factors in Mrsa and Mssa Isolated From Different Clinical Cases - Noora Hamid Ibrahim1 , Ahmed Mohammed Turki2 , Jamal Abd Al-Rahman3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The current study included the collection of 100 clinical samples obtained of patients reviewed inthe laboratories of Ramadi hospital for women and children and Hit General Hospital and some civillaboratories within the city of Ramadi, including Bacterimea samples, Urine, abscesses, heart inflammation,wounds, rhinitis, osteoporosis, otitis ,Laryngitis, sputum (35, 20, 5, 6, 7, 5, 8, 7, 4, 3) samples respectivelyto investigate the presence of staphylococcus aureas . The results of diagnosis of bacterial isolates showedthat there were 55 bacterial isolates belonging to the S.aureus bacteria after they were grown on the culturemedia and examined microscopic as well as the use of some of the tests on the chemical, and the diagnosiswas confirmed using the Vitek2-compact system .The diagnostic results were confirmed by the use ofgenetic diagnosis. The results of the phenotypic investigation were identical to the results of the geneticinvestigation using the polymerase chain reaction technique in terms of possessing isolates producing bothhemolycin , on the HlA encoding genes for the production of type and hlB encoded for typeproduction, For plasma blood on the co-a gene, and the resistance isolates of methylation on the mecA gene.